EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION AND BENSON RELAXATION THERAPY ON BLOOD PRESSURE AMONG HYPERTENSIVE ELDERLY AT ANYELIR INTEGRATED HEALTH POST, CIJANTUNG, EAST JAKARTA IN 2025 - Enggrit Elita Patria (Jurnal Medika Hutama, 2026)
Background: Hypertension is a global health challenge affecting 1.28 billion adults worldwide (WHO, 2021). In Indonesia, prevalence reaches 34.1%, with the elderly aged 65-74 years having the highest risk at 63.2%. Effective, simple, and low-cost non-pharmacological interventions are needed alongside pharmacological therapy to control blood pressure.Objective: This study aimed to compare the effectiveness of Benson Relaxation Therapy and Progressive Muscle Relaxation (PMR) on blood pressure in elderly patients with hypertension at Anyelir Integrated Health Post, Cijantung, East Jakarta.Methods: A quasi-experimental design with a pre-post test two-group approach was used. Forty elderly respondents with hypertension were selected using purposive sampling and divided equally into the Benson Relaxation group (n=20) and the PMR group (n=20). Each intervention was conducted for 15 minutes per session over two weeks. Blood pressure was measured before and after the intervention. Data were analyzed using the Paired T-Test with a significance level of p<0.05.Results: Both interventions significantly reduced blood pressure (p=0.000). The Benson Relaxation group showed a mean systolic reduction of 10.45 mmHg and diastolic reduction of 7.85 mmHg. The PMR group showed a mean systolic reduction of 10.25 mmHg and diastolic reduction of 7.70 mmHg. There was no statistically significant difference between the two groups, although Benson Relaxation showed a slightly greater descriptive reduction.Conclusion: Benson Relaxation Therapy and Progressive Muscle Relaxation are both effective in reducing blood pressure in hypertensive elderly. Both methods are recommended as complementary therapies for blood pressure management in community health settings such as Posyandu.Keywords: Benson Relaxation, Progressive Muscle Relaxation, Blood Pressure, Hypertension, Elderly